AGRIBISNIS NENAS DI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Jum’atri Yusri; Novia Dewi; Satria Gunawan (Indonesian Journal of Agricultural Economics, 2020)
The purposes of this research are mention as follows : 1) To know the condition of Pineapple agribusiness’ subsystems at Kecamatan Tanah Putih,  2) to analyze the income of Pineapple’s farming at kecamatan tanah putih.  This research was conducted at Kecamatan Tanah Putih Kabupaten Rokan Hilir with the amount of sample is 32 person through survey method. This was descriptive analysis research. The research result that drawn on supply of subsystem and production of facility supply shown that the 6 criteria direct on seeds, fertilizer, pesticide,and Pineapple farming equipment which exist at Kecamatan Tanah Putih were already proper as its supply, affordable, and available at the research location. The production of Pineapple at Kecamatan Tanah Putih Kabupaten Rokan Hilir on average were 8.400 pieces/ha/year,  cost on average Rp. 12.423.300-/ha/year. Gross income as much as Rp. 33.600.000-/ha/year, net income as much as Rp. 20.174.300-/ha/year, RCR as much as 2,5.  The application of subsystem were not went well, it is caused by the farmers were not able to process the Pineapples into valuable items such as pineapple chips or other. There were 4 marketing channels. The farmers of pineapple only have 2 marketing channels as a producer which is marketing channel to intermediary traders and marketing channel directly to the consumers. The farmers tend to choose the marketing channels through the intermediary traders. The supporting institutions of pineapple farming have not runs maximally.